Review of educational research on drop-out. Bibliometric trends (Research, Society and Development, 2021)
The purpose of this article is to carry out a bibliometric analysis of one of the educational problems with the greatest recurrence in education systems, school drop-out. This emerges from the numerous attempts that, both administration and research, have been made to achieve a formula that manages to alleviate the high incidence of this phenomenon. Which, as can be seen, has been a problem of interest in presenting the already overdue Strategy for Europe Horizon 2020 and being considered key to the 2030 Sustainable Development Goals. The research will be carried out through a bibliometric analysis of the databases with the highest representation in the educational field: ERIC, Dialnet, Teacher Reference Center, Web of Science and Scopus. After establishing the descriptors and criteria of inclusion/exclusion, 210 references were extracted in which the specific topic was analyzed within the educational abandonment, the main authors in the field of research and the main publications on this educational problem, among others.